INFLUENCE ANALYSIS OF ACTION ON THE ILLUSION OF CONTROL - Rovira Faixa, Tatiana; Fernández Castro, Jordi; Edo Izquierdo, Silvia (Anales de Psicología / Annals of Psychology, 2000)
This essay assesses the importance of action in generating illusion of control. We have used three noncontingent tasks based on the paradigm of contingency judgements. One of them allows voluntary action, another presents a guided action and the last one, without action, only allows to make predictions. Judgements made by the subjects in each of these tasks indicate that they generate a higher illusion of control in those situations where they can decide their action. Also, although with a lower degree, overestimation of judgement appears in the other two tasks too, which show equal judgements yet apparently differing in the underlying reasoning which led to them. Results are discussed in relation with supposedly divergent theoretical positionings as found in Thompson, Armstrong and Thomas (1998) and Teigen (1994).